Human cytomegalovirus UL69 protein facilitates translation by associating with the mRNA cap-binding complex and excluding 4EBP1 - Aoyagi, Mariko (National Academy of Sciences, 2010)
4EBP1 is phosphorylated by the mTORC1 kinase. When mTORC1 activity is inhibited, hypophosphorylated 4EBP1 binds and sequesters eIF4E, a component of the mRNA cap-binding complex, and blocks translation. As a consequence, mTORC1 activity is needed to maintain active translation. The human cytomegalovirus pUL38 protein preserves mTORC1 activity, keeping most of the E4BP1 in the infected cell in a hyperphosphorylated, inactive state. Here we report that a second viral protein, pUL69, also antagonizes the activity of 4EBP1, but by a separate mechanism. pUL69 interacts directly with eIF4A1, an element of the cap-binding complex, and the poly(A)-binding protein, which binds to the complex. When pUL69 accumulates during infection with wild-type virus, 4EBP1 is excluded from the complex. However, 4EBP1 is present in the cap-binding complex after infection with a pUL69-deficient virus, coincident with reduced accumulation of several late virus-coded proteins. We propose that pUL69 supports translation in human cytomegalovirus-infected cells by excluding hypophosphorylated 4EBP1 from the cap-binding complex.